2013
DOI: 10.1371/journal.pone.0072739
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the Retinoic Acid Metabolizing Enzyme CYP26B1 and the Development of Crohn’s Disease

Abstract: Several studies suggest that Vitamin A may be involved in the pathogenesis of inflammatory bowel disease (IBD), but the mechanism is still unknown. Cytochrome P450 26 B1 (CYP26B1) is involved in the degradation of retinoic acid and the polymorphism rs2241057 has an elevated catabolic function of retinoic acid, why we hypothesized that the rs2241057 polymorphism may affect the risk of Crohn’s disease (CD) and Ulcerative Colitis (UC). DNA from 1378 IBD patients, divided into 871 patients with CD and 507 with UC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…They individually affect the metabolism of drugs or endogenous compounds. Little is known with respect to carotenoids, but it was shown that a polymorphism regarding CYP26B1 (rs2241057) influences the degradation of retinoic acid, and is likely related to the risk of Crohn's disease and atherosclerosis .…”
Section: Further Transport and Biodistribution To Potential Target Timentioning
confidence: 99%
“…They individually affect the metabolism of drugs or endogenous compounds. Little is known with respect to carotenoids, but it was shown that a polymorphism regarding CYP26B1 (rs2241057) influences the degradation of retinoic acid, and is likely related to the risk of Crohn's disease and atherosclerosis .…”
Section: Further Transport and Biodistribution To Potential Target Timentioning
confidence: 99%
“…() reported the presence of an additional tooth in the ventral row, posterior to the tooth position 5V, in wild‐type zebrafish ( cyp 26b1 +/+) treated with all‐trans retinoic acid, and for the heterozygous adult zebrafish mutant stocksteif ( sst ) ( cyp 26b1 +/−). The gene cyp 26b1 encodes for an enzyme involved in the degradation of retinoic acid (Fransén et al., ) and thus the zebrafish mutant stocksteif possesses dentitions similar to wild‐type zebrafish treated with exogenous retinoic acid. The digitalized microtomography image of the dentition of an adult stocksteif mutant, shown in the article, indeed reveals a supernumerary tooth in the ventral row, albeit that the tooth is located anterior to 1V, not posterior to 5V.…”
Section: Discussionmentioning
confidence: 99%
“…A polymorphic variation rs2241057C/C (minor allele) L264S is associated with larger macrophage-positive atherosclerotic lesions, whereas carries of the major allele rs2241057T/T have an increased risk of Crohn's disease, an autoimmune condition of the gut. Additionally, Cyp26b1 is upregulated in atheroschlerotic lesions and associated there with activated macrophages, suggesting that Cyp26b1 may be important in RA clearance in the arterial wall [215][216][217]. Neural tube, limb, craniofacial, skeletal, heart, kidney and lung defects [207] (samples collected during gestation) Several papers have reported human skeletal abnormalities in patients with CYP26B1 mutations.…”
Section: Cyp26 In Human Genetic Diseasementioning
confidence: 99%